Celebrity Worship : A Scoping Review - Kusmawan, Putri Fitriani Diah; Yunita Sari (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Celebrity worship as a type of worship of people who are widely famous and attract the attention of the public as well as the media. In recent years celebrity culture and entertainment have grown rapidly to become extremely popular among people of all ages. Fans have shown their admiration and devotion to celebrities, as well as a strong desire to follow their every action. The purpose of this study is to explore the development of topics related to celebrity worship. Scoping the review to map the topic of celebrity worship, six databases were explored in the literature review. In writing the literature review, 60 article titles were found and then 13 articles that fit the criteria were selected. The findings showed that celebrity worship is related to demographic factors such as age and gender, mental health conditions, eating disorder behaviors and body image, impulse buying, social relationships, and social media. The results of the review can be used to help researchers understand the various factors related to celebrity worship. Abstrak. Celebrity worship sebagai suatu jenis pemujaan terhadap orang yang terkenal secara luas dan menarik perhatian publik juga media. Dalam beberapa tahun terakhir budaya selebritas dan hiburan telah berkembang pesat menjadi sangat populer di kalangan orang-orang dari segala usia. Para penggemar telah menunjukkan kekaguman dan pengorbanan mereka kepada para selebriti, serta keinginan yang kuat untuk mengikuti setiap tindakan mereka. Tujuan dari penelitian ini adalah untuk mengeksplorasi perkembangan topik-topik yang berkaitan dengan celebrity worship. Scoping review dimaksudkan untuk memetakan topik celebrity worship, enam database ditelusuri dalam tinjauan literatur. Dalam penulisan tinjauan literatur, 60 judul artikel ditemukan kemudian terpilih 13 artikel yang sesuai dengan kriteria. Temuan menunjukkan bahwa celebrity worship berkaitan dengan faktor demografi yaitu usia dan gender, kondisi kesehatan mental, perilaku gangguan makan dan citra tubuh, impulse buying, relasi sosial, serta media sosial. Hasil tinjauan tersebut dapat digunakan untuk membantu peneliti memahami berbagai faktor yang berkaitan dengan celebrity worship.